2019
DOI: 10.1186/s12889-019-7936-1
|View full text |Cite
|
Sign up to set email alerts
|

Campbelltown – Changing our Future: study protocol for a whole of system approach to childhood obesity in South Western Sydney

Abstract: BackgroundIn Australia, around 67% of adults and 25% of children (5–17 years) are currently overweight or obese (Australian Bureau of Statistics, 4364.0.55.001 - National Health Survey: First Results, 2017–18, 2018). The Campbelltown – Changing our Future study will translate ‘a whole of system’ approach, previously trialed in rural communities in Victoria and the Australian Capital Territoty, to Campbelltown Local Government Area (LGA), a socioeconomically and ethnically diverse urban community in south weste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…This includes the formation of an interdisciplinary consortium of scientists and societal partners, the latter embedded within the AHWP. The AHWP, in itself, provides an exceptional opportunity to achieve the ambitions of the LIKE programme, facilitated by the unique combination of conditions created over the past years, including strong political support, commitment and involvement of community organisations in the objectives of the programme, and involvement of public sectors other than public health (e.g., education, spatial planning) [59]. This means that we do not have to start from scratch in creating community or policy involvement and that a lot of the networks and structures already exist.…”
Section: Discussionmentioning
confidence: 99%
“…This includes the formation of an interdisciplinary consortium of scientists and societal partners, the latter embedded within the AHWP. The AHWP, in itself, provides an exceptional opportunity to achieve the ambitions of the LIKE programme, facilitated by the unique combination of conditions created over the past years, including strong political support, commitment and involvement of community organisations in the objectives of the programme, and involvement of public sectors other than public health (e.g., education, spatial planning) [59]. This means that we do not have to start from scratch in creating community or policy involvement and that a lot of the networks and structures already exist.…”
Section: Discussionmentioning
confidence: 99%
“…Key components of the intervention include; stakeholder-informed development of CLDs, development of locally-tailored action in response to the drivers of childhood obesity as described in the CLD, formation of key stakeholder and community working groups to prioritise and implement actions, and continuous monitoring of intervention actions. The full protocol for the Change4Campbelltown initiative is published elsewhere [ 17 ], and primary and secondary analyses of the main study outcomes will be presented in future publications.…”
Section: Methodsmentioning
confidence: 99%
“…In 2017, the Campbelltown - Changing our Future (Change4Campbelltown) [ 17 ] initiative brought together key leaders, the school-sector and community members to translate a ‘whole of system’ approach, previously trialled in rural and regional Australian communities, to the Campbelltown Local Government Area (LGA) in south west Sydney, Australia. The initiative began with the development of a stakeholder-informed CLD, reflecting the underlying logic of obesity drivers for the Campbelltown community, and providing the basis for community-led intervention design.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of research aims found in the 23 articles, four themes emerged: 1) to examine the complexity of a public health topic and illustrate complex systems thinking [26][27][28][29][30][31][32][33][34]; 2) to discuss the complexity of a public health intervention [35][36][37][38][39][40]; 3) to describe study protocol and how CLDs were created [41][42][43][44]; and 4) to illustrate how CLDs can be used to monitor and track initiatives to improve population health or evaluate impact of interventions [45][46][47][48].…”
Section: Research Aimsmentioning
confidence: 99%
“…Both primary and secondary data were used for creating CLDs (Table 3). Most articles reported on primary data collection (18/ 23) and this included interviews [26,27,33,[35][36][37][38][39][40], group model building with stakeholders and/or community members [32,41,43,44,46,48], behavioral data [42,47], fieldnotes [37], and workshops with experts [31]. Twelve articles used primary data only.…”
Section: Data Sourcesmentioning
confidence: 99%